Akibat Hukum Berlakunya Perma Nomor 02 Tahun 2012 Tentang Penyesuaian Batasan Tindak Pidana Pencurian Ringan Dan Jumlah Denda Dalam KUHP - Hasiholan Naibaho; Isnaini Isnaini; Marlina Marlina (Mahesa Research Center, 2021)
By issuing Supreme Court Regulation Number 2 of 2012 concerning Limits of Minor Crimes and the Amount of Fines in the Criminal Code in order to resolve minor crimes. After the issuance of the PERMA, a new problem arose because the PERMA was not used in the settlement of minor criminal cases. This causes legal uncertainty after the issuance of PERMA No. 2 of 2012. This thesis uses normative legal research, namely research that refers to legal norms contained in laws and regulations that apply as a normative footing. The legal rules limiting minor crimes and the amount of fines in the Criminal Code with the issuance of Supreme Court Regulation Number 02 of 2012 namely: Legal Position Supreme Court Regulation Number 2 of 2012 substantially relates to adjustments to the limits of minor crimes and the amount of fines. The implementation of the law against the crime of minor theft after the issuance of the Supreme Court Regulation Number 02 of 2012 concerning minor crimes is as follows: The existence of Perma No. 2 of 2012 is a Criminal Policy and so far criminal policy is understood as the domain of the Criminal Justice System (SPP) which implements the representation of the state. In addition, criminal policy is also better understood as a way to enforce the law in the context of crime prevention. Constraints faced by law enforcement officers of the Police. Constraints in law enforcement occur when there is a discrepancy between value pairs and this discrepancy can be caused by: understanding of the police regarding the regulation, the courage of the police officers without overlapping, socialization of the regulation and shaping community culture